Video tutorial-based learning media: A solution to assist students in learning sepaksila sepaktakraw skills - I Ketut Semarayasa; Peby Gunarto; Ketut Karin Preayani (Journal Sport Area, 2023)
The use of video learning media has been believed to play an important role in facilitating the teaching and learning process. However, limited video learning media are available for teaching the sepak takraw course. To fill this need, this research aimed at developing a video tutorial to assist students in learning the sepak sila skill at the sepak takraw course. The study applied research and development (R & D) design with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data were collected through a questionnaire and an interview. A questionnaire was used to collect the students’ needs, the validity of the product, and the students’ perceptions about the product. An interview was conducted to seek feedback from the experts (a content expert, a design expert, a learning media expert, and a practitioner or coach) related to the developed product. The data were analyzed quantitatively and qualitatively. The results show that the developed product was feasible to use. This was proven by the average score of the product validity, which was 4,7 (very good). The results of the field trials also showed very good results (4, 8). The students perceived the developed product positively, in that it could arouse their motivation to learn, was easy to understand and follow, and could help them enhance their sepak takraw skills. The study's findings could enrich existing theories about the importance of using learning media in teaching as well as provide a practical contribution in that the developed product can be used by both sepak takraw lecturers and students to improve students' sepak takraw skills.